Comparison of six commercial systems for the detection of non-O157 STEC in meat and vegetables - Costa, Magdalena; Sucari, Adriana; Epszteyn, Sergio; Oteiza, Juan Martín; Gentiluomo, Jimena; Melamed, Celia; Figueroa, Yamila; Mingorance, Santiago Emmanuel; Grisaro, Agustina; Spioussas, Silvia; Buffoni Almeida, Mariana; Caruso, Mailen; et al. (Elsevier, 2019)
Shiga toxin-producing Escherichia coli (STEC) are important pathogens transmitted by food that may cause severe illness in human beings. Thus, systems for STEC detection in food should have increasingly higher sensitivity and specificity. Here we compared six commercial systems for non-O157 STEC detection in meat and vegetables and determined their sensitivity, specificity and repeatability. A total of 46 samples (meat n = 23; chard n = 23) were experimentally contaminated with strains O26:H11, O45:H-, O103:H2, O111:NM, O121:H19 and O145:NM isolated in Argentina. Strain detection was confirmed by isolation according to ISO 13136:2012. Detection of the stx and eae genes in meat samples was highly satisfactory with all commercial kits, but only five had 100% sensitivity and specificity in chard. Of four kits evaluated for serogroup detection, three had 100% sensitivity and specificity, and one had 93.7% sensitivity and 100% specificity. All kits were adequate to analyze meat but not vegetable samples, and were not therefore validated for the latter matrix. The challenge for microbiology laboratories is to identify the advantages and disadvantages of the available kits for STEC detection in food based on a clear knowledge of the particular needs of each laboratory.